2019
DOI: 10.4028/www.scientific.net/msf.958.11
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Catalysts Mordenite and MoO<sub>3</sub>/Mordenite in the Production of Biodiesel

Abstract: The world's energy production is generated mainly from fossil fuels, so it is important to develop fuels from renewable sources. Growing caution with the environmental impact imposes restrictions on emissions from the combustion of fossil fuels. With increasing human population and expanding economies in both developing and developed countries, there is an increase in energy consumption and production. The need arises to supply this high energy production with a renewable and reliable source fuel [1]. These fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Results reported in Table 1 represent various catalysts prepared and characterized by different authors for biodiesel production by transesterification of vegetable oil reported in the literature [29][30][31][32]. In order to compare the performance of the catalyst prepared in this literature (MoO 3 /Mordenite zeolite) with recent studies, despite the experimental conditions being very different, it is possible to conclude that the catalyst prepared in this work is promising.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Results reported in Table 1 represent various catalysts prepared and characterized by different authors for biodiesel production by transesterification of vegetable oil reported in the literature [29][30][31][32]. In order to compare the performance of the catalyst prepared in this literature (MoO 3 /Mordenite zeolite) with recent studies, despite the experimental conditions being very different, it is possible to conclude that the catalyst prepared in this work is promising.…”
Section: Introductionmentioning
confidence: 95%
“…The authors [32] has been studied the catalytic performance of mordenite and MoO 3 /MOR for the transesterification of soybean oil using a batch reactor at 200°C. The effects of catalyst (Mordenite and MoO 3 /MOR) on the kinematic viscosity of produced biodiesel and conversion were investigated.…”
Section: Introductionmentioning
confidence: 99%